The Effect of Promotion and Service Quality on Purchase Decisions for Nasa Products at Nasa Tasikmalaya Stockists - Dini Lestari; Depy Muhamad Pauzy; Suci Putri Lestari (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the effect of promotion and service quality on purchasing decisions for Nasa products at Nasa Stockists Tasikmalaya. The type of research used is quantitative research with causality method and survey approach. Sampling used incidental sampling of 100 respondents using multiple linear regression analysis techniques. The results of this study indicate that promotion and service quality simultaneously have a significant effect on purchasing decisions for Nasa products at Nasa Stockists Tasikmalaya. Promotion and service quality partially have a significant effect on purchasing decisions for Nasa products at Nasa Stockists Tasikmalaya.